2021
DOI: 10.1111/jopr.13272
|View full text |Cite
|
Sign up to set email alerts
|

Marginal and Internal Adaptation of Lithium Disilicate Endocrowns Fabricated By Heat‐Pressable and Subtractive Techniques

Abstract: Purpose To evaluate and to compare the marginal and the internal fit of milled (MLE) and heat‐pressed lithium disilicate endocrowns (PLE). Materials and Methods Thirty mandibular molars were prepared following the circumferential butt margin endocrown preparations; the cervical margin is parallel to the occlusal surface without ferrule design. A digital scan of molars was made using an intraoral digital scanner. The samples were separated into two groups (n = 15 per group); MLE: endocrowns were milled using LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…A nondestructive replica technique (RT) has been chosen to evaluate the adaptation of endocrowns. The RT has been selected to evaluate marginal and internal discrepancies by previous studies (El Ghoul & Salameh, 2021;Hasanzade et al, 2020;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A nondestructive replica technique (RT) has been chosen to evaluate the adaptation of endocrowns. The RT has been selected to evaluate marginal and internal discrepancies by previous studies (El Ghoul & Salameh, 2021;Hasanzade et al, 2020;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21]. Also there is other study shown the marginal adaptation of CAD/CAM endocrown had superior marginal seating than a classical full crowns [22].…”
Section: Discussionmentioning
confidence: 99%
“…Для оцінки крайової та внутрішньої адаптації використовували стереомікроскоп та метод реплік. Дослідження показало, що обидва підходи є клінічно прийнятними, хоча метод фрезерування перевершив метод термопресування [13].…”
Section: рис 1 стратегія пошуку наукових джерелunclassified